Factors Affecting Security Information Systems : Information Security, Threats and Cyber Attack, Physical Security, and Information Technology - Lestari, Dwi Puji; Tama, Andika Lutfhi Citra; Karlina, Siti; Sultan, Achmad; Tarwoto, Tarwoto (International Journal of Informatics and Information Systems, 2024)
Information systems are very important to support various organizational and individual activities. Therefore, information system security is an important issue in today's digital era, where it is very important to pay attention to the protection of sensitive data and information. This research aims to identify and analyze factors that influence information system security. These factors include information system security, cyber threats and attacks, physical security, and information technology. Each factor is thoroughly analyzed to understand its impact on information system security. The results of this research will help improve our understanding of the factors that influence information system security. These findings can be used as a basis for creating effective security policies in protecting the information assets owned by the organization. By understanding these things, organizations can optimize their security efforts against the ever-evolving security threats in today's digital world.